Conceptual understanding of provider responses to the complexity of healthcare delivery - Arnold, Tracey; Polifroni, E. C. (Mental health and wellness in healthcare workers: Identifying risks, prevention, and treatment: Identifying risks, prevention, and treatment, 2022)
Keywords: dept.nur

Diabetes Distal Peripheral Neuropathy: Subtypes and Diagnostic and Screening Technologies - Newlin Lew, Kelley; Arnold, Tracey; Cantelmo, Catherine; Jacque, Francky; Posada-Quintero, Hugo; Luthra, Pooja; Chon, Ki H. (Journal of Diabetes Science and Technology, 2022)
Diabetes distal symmetrical peripheral neuropathy (DSPN) is the most prevalent form of neuropathy in industrialized countries, substantially increasing risk for morbidity and pre-mature mortality. DSPN may manifest with small-fiber disease, large-fiber disease, or a combination of both. This review summarizes: (1) DSPN subtypes (small- and large-fiber disease) with attention to clinical signs and patient symptoms; and (2) technological diagnosis and screening for large- and small-fiber disease with inclusion of a comprehensive literature review of published studies from 2015-present (N = 66). Review findings, informed by the most up-to-date research, advance critical understanding of DSPN large- and small-fiber screening technologies, including those designed for point-of-care use in primary care and endocrinology practices.
Keywords: dept.nur; peer-reviewed

Differences in Neonatal Outcomes Among Premature Infants Exposed to Mother's Own Milk Versus Donor Human Milk - Cartagena, Diana; Penny, Frances; McGrath, Jacqueline M.; Reyna, Barbara; Parker, Leslie A.; McInnis, Joleen (Advances in Neonatal Care: Official Journal of the National Association of Neonatal Nurses, 2022)
BACKGROUND: Growing evidence supports the superior benefits of exposure to mother's own milk (MOM) in reducing prematurity-related comorbidities. Neonatal exposure to donor human Milk (DHM) is a suitable alternative when MOM is insufficient or unavailable. However, the same protective composition and bioactivity in MOM are not present in DHM. Additional evidence is needed to justify and inform evidence-based practices increasing MOM provision while optimizing adequate use of DHM for premature infants. PURPOSE: A systematic review of the literature was conducted to determine differences in neonatal outcomes among premature infants exposed to predominately MOM versus DHM. METHODS/SEARCH STRATEGY: Databases including PubMed, CINAHL and Cochrane were searched (2020-2021) using the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analysis) guidelines. Evidence was classified using the John Hopkins evidence-based practice levels and quality of evidence. RESULTS: Eleven studies met inclusion criteria. Studied neonatal outcomes included ( a ) growth parameters (n = 8), ( b ) neonatal morbidities (n = 6), and ( c ) gut microbiome (n = 4). Overall, evidence suggests DHM exposure is beneficial but not equivalent to MOM feeding. Compared with DHM, greater doses of MOM are ideal to enhance protection primarily related to infant growth, as well as gut microbiome diversity and richness. IMPLICATIONS FOR PRACTICE: Standardized and evidence-based practices are needed to clearly delineate optimal use of DHM without undermining maternal and neonatal staff efforts to support and promote provision of MOM. IMPLICATIONS FOR RESEARCH: Additional evidence from high-quality studies should further examine differences in neonatal outcomes among infants exposed to predominately MOM or DHM in settings using standardized and evidence-based feeding practices.
Keywords: Breast Feeding; Female; Humans; Infant; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Intensive Care Units, Neonatal; Milk, Human; Mothers; dept.nur; peer-reviewed

Fostering Nursing Students' Moral Decision-Making Through Use of an Affective Learning Module - Morrill, Deborah; Westrick, Susan J. (Nurse Educator, 2022)
Background: The emphasis on disciplinary and preventive approaches to combating academic misconduct does little to foster student professional identity and core nursing value formation. Problem: There is a need for pedagogy designed to navigate moral decision-making within ambiguous areas of practice as nursing students integrate personal and professional values while becoming a nurse. Approach: Rest's theory of moral development offers a framework for constructing purposeful affective learning activities that operationalize moral sensitivity, judgment, motivation, and character, whereas Krathwohl's theory provides a means to identify affective learning objectives. Offering prelicensure nursing students an opportunity to discuss, reflect on, and consider actions and consequences associated with academic and practice-based situations forms the basis for this affective learning module that fosters connections between academic and professional behaviors of integrity. Conclusion: Rest's theoretical model provides a viable structured approach to moral development. Curriculum designed to engage moral decision-making offers an innovative approach to cultivating student integrity.
Keywords: dept.nur; peer-reviewed

And sometimes, we say good night - Green, C. (International Journal of Africa Nursing Sciences, 2022)
The evolution of life is that one day after we are born, we must say good night, and fall asleep and breath no more. The trepidation of death is more than the ceasing of lung, cardiac, and brain function; for the nurse who loses a nurse colleague, it is a farewell of a collegial relationship that developed in the process of healing others. The death of a nurse colleague is sacred. © 2022
Keywords: article; bereavement; brain function; breathing; dept.nur; grief; heart function; human; lung function; night; nurse; peer-reviewed; terminal care

Applying the nightingale pledge in reducing health disparities: A hospital-acquired pressure injury case study - Green, C. (Advances in skin & wound care, 2022)
ABSTRACT: Professional nurses, by virtue of their training, pledge to care for individuals who are sick or infirm. This commitment is confirmed via the Nightingale Pledge, which focuses on public health and equity and deems the nurse to be a missioner of health. Health disparities exist in direct conflict with the nursing responsibility of caritas, or love. Accordingly, it is imperative that nurse educators create learning environments that are conducive to comfortably discussing differences in physical assessments performed on diverse populations as part of their work to eliminate health disparities and in accordance with the Nightingale Pledge. Copyright © 2022 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: Hospitals; Humans; dept.nur; hospital; human; peer-reviewed